Multistatic sensing for target localization in ISAC systems - Zhuge, Shun (Nanyang Technological University, 2024)
Integrated sensing and communication (ISAC) plays a vital role as a foundational technology for upcoming wireless communication standards. Current research focuses on investigating the use of a standardized communication waveform to obtain radar parameters while performing communication functions simultaneously, known as communication-centric ISAC design. However, the radar parameters obtained through the ISAC receiver may differ from those of traditional radar, and not all traditional sensing models are suitable for ISAC applications. Therefore, dedicated localization algorithms are needed for sensing functions in the ISAC system. This dissertation explores innovative and sophisticated approaches for localizing moving targets using multistatic sensing within the ISAC framework. Two geometric solutions for target localization are proposed using radar parameters obtained from the ISAC receiver, including the bistatic range (BR), the bistatic range rate (BRR), and the direction of arrival (DOA). The first localization algorithm can estimate the position and the velocity of a moving target in an ISAC system with static transmitters, such as base stations. The second localization algorithm operates when transmitters are mobile, such as user equipment (UE). The proposed localization algorithms aim to overcome the limitations of existing multistatic sensing algorithms, specifically the two-step weighted least square (2SWLS) methods, by addressing the minimum requirements of available transmitter-receiver pairs. Additionally, the two proposed methods demonstrate superior performance compared to existing 2SWLS methods, particularly in accurately estimating the position and velocity of the target under identical circumstances.